SPATIAL ANALYSIS IN THE DEVELOPMENT OF THE ECONOMIC AREA OF COASTAL VILLAGE KALANGANYAR - Yunisya, Adibah Nurul; Elviana, Eva; Mutia, Fairuz (Border: Jurnal Arsitektur, 2021)
Kalanganyar Village is a coastal village located on the coast of Sidoarjo Regency. Like other coastal villages, Kalanganyar Village carries a special coastal character both in the livelihood sector, land use sector, potential natural disaster sector, and socio-economic sector. Several studies show that the socioeconomic conditions of coastal communities live below the poverty line, while the lives of coastal communities depend a lot on land use in coastal areas (ponds and sea). Clasification and phenomena of coastal areas are strongly defined by the spatial character of the coast which is located on the boundary of land and sea. Therefore, this study intends to look at the economic condition of the coastal community of Kalanganyar Village by analyzing the spatial conditions of the area. Researchers will observe how the development of the economic area of Kalanganyar Village from time to time spatially. The spatial data obtained will be analyzed by taking into account the existing condition of infrastructure, potential disasters, and the existing condition of livelihood diversification of the residents of Kalanganyar Village. From the results of the analysis, it was found that infrastructure development also contributed to the development of the economic area of Kalanganyar Village. The results of historical observations of the development of the region show stagnant development due to the cessation of infrastructure development in the Kalanganyar Village area, so that the people of Kalanganyar Village cannot create diversification of employment opportunities in their region.